Role of Ship-Breaking Industries in Bangladesh and ILO Guidelines: A Critical Discussion (Global Journal of Human-Social Science, 2016)
Introduction-Ship-breaking is a risky, dirty, intensively labour-manipulating and hazardous industry. 'A ship's life lasts for an average of 25 to 30 years after which they are no longer considered safe to sail. Each year between 200 and 600 sea-going ships are dismantled worldwide. A peak is expected in 2010 when around 800 single-hull tankers will have to be phased out' (European Commission Report, 2007). It is only few decades earlier that European countries and the United States had the sole authority of both ship-sailing and ship-breaking around the world. Therefore, they made profits in both ways. During the last two decades, developed countries has lost its sole authority over ship dismantling business because of increasing wage rate, increasing awareness towards global environment, raising safety and health consciousness among workers of developed countries. A report of the European Commission mentioned that 'a worker on demolition site in Bangladesh and India earns just one to two dollars per day, and employers' expenses for safety and health are negligible; while the cost in the Netherlands can be estimated at around $250 per day for a worker in the Netherlands, and $13 in Bulgaria (EU Reports, 2007).